Ventilation management and outcomes in out-of-hospital cardiac arrest: a protocol for a preplanned secondary analysis of the TTM2 trial - Robba, Chiara; Nielsen, Niklas; Dankiewicz, Josef; Badenes, Rafael; Battaglini, Denise; Ball, Lorenzo; Brunetti, Iole; Pedro David, Wendel-Garcia; Young, Paul; Eastwood, Glenn; Chew, Michelle S; Jakobsen, Janus; et al. (BMJ open, 2022)
INTRODUCTION: Mechanical ventilation is a fundamental component in the management of patients post cardiac arrest. However, the ventilator settings and the gas-exchange targets used after cardiac arrest may not be optimal to minimise post-anoxic secondary brain injury. Therefore, questions remain regarding the best ventilator management in such patients. METHODS AND ANALYSIS: This is a preplanned analysis of the international randomised controlled trial, targeted hypothermia versus targeted normothermia after out-of-hospital cardiac arrest (OHCA)-target temperature management 2 (TTM2). The primary objective is to describe ventilatory settings and gas exchange in patients who required invasive mechanical ventilation and included in the TTM2 trial. Secondary objectives include evaluating the association of ventilator settings and gas-exchange values with 6 months mortality and neurological outcome. Adult patients after an OHCA who were included in the TTM2 trial and who received invasive mechanical ventilation will be eligible for this analysis. Data collected in the TTM2 trial that will be analysed include patients' prehospital characteristics, clinical examination, ventilator settings and arterial blood gases recorded at hospital and intensive care unit (ICU) admission and daily during ICU stay. ETHICS AND DISSEMINATION: The TTM2 study has been approved by the regional ethics committee at Lund University and by all relevant ethics boards in participating countries. No further ethical committee approval is required for this secondary analysis. Data will be disseminated to the scientific community by abstracts and by original articles submitted to peer-reviewed journals. TRIAL REGISTRATION NUMBER: NCT02908308.
Keywords: Adult; dospělí; randomizované kontrolované studie jako téma; Intensive Care Units; umělé dýchání; hospitalizace; lidé; jednotky intenzivní péče; Hospitalization; Randomized Controlled Trials as Topic; Out-of-Hospital Cardiac Arrest; Respiration, Artificial; Humans; zástava srdce mimo nemocnici